INTERFERENSI FONOLOGI DAN MORFOLOGI PADA TEKS DESKRIPSI SISWA SMP BESERTA TEKNIK MINIMALISASI: PHONOLOGICAL AND MORPHOLOGICAL INTERFERENCE IN DESCRIPTIVE TEXTS BY SECONDARY SCHOOL STUDENTS AND TECHNIQUES FOR MINIMISING IT - Yulia Aslamiyah; Atiqa Sabardila; Markhamah (Satya Widya, 2026)
This study examines the phenomena of language interference that naturally arise when lower secondary school pupils use Indonesian as a second language in writing activities. The aim of this study is to identify various forms of language interference occurring at the phonological and morphological levels in descriptive texts written by pupils, whilst also analysing the factors that cause such interference to occur. The method used in this study is a qualitative descriptive method employing a comparative analysis technique between Indonesian language structures that conform to linguistic norms and the language system commonly used by students in their daily lives as their first language. The results of the study indicate that the most dominant interference is found in the phonological aspect, for example, the change of the sound /p/ to /b/, /u/ to /o/, and /a/ to /e/. Furthermore, interference is also evident in the morphological aspect, such as the use of the suffix -an, the use of reduplication forms, and the combination of words that do not conform to the rules of word formation in Indonesian. The emergence of this phenomenon is influenced by the widespread use of Javanese in everyday communication, oral language habits, and students’ still limited mastery of the written rules of Indonesian.